The Effect of the Video Demonstration Method on Students' Understanding of Fiqh Subjects for Fardhu Prayer Materials at Madrasah Ibtidaiyah During the Covid-19 Pandemic: Pengaruh Metode Demonstrasi Melalui Video Terhadap Pemahaman Siswa Pada Mata Pelajaran Fiqih Materi Sholat Fardhu Di Madrasah Ibtidaiyah Saat Pandemi Covid-19 - Amilatul Rosidah; Ruli Astuti (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of learning using the demonstration method on student understanding and how much influence it has. With the selection of methods that are in accordance with the characteristics of the subject matter, it is expected to increase students' understanding so as to reduce the occurrence of verbalism. This type of research is quantitative with a quasi-experimental method consisting of an experimental class and a control class. The sample in each class is 10. The data collection technique uses a test, namely an objective test of 10 questions and a subjective test of 5 questions. The results showed that the effect of the demonstration method on students' understanding which can be seen from the analysis of the